Comparison of Research Designs for Two Controlled Trials of Mass Media Interventions - Flynn, Brian S. (2009)
This paper compares two controlled trials of mass media interventions, factors influencing their designs, and design lessons learned from these experiences. Mass media evaluations based on a scientific research model are motivated by gaps in knowledge. The results of such research are intended to serve the needs of consensus development processes through which confident recommendations can be made for intervention strategies that should be more widely applied. For these purposes, the scientific research context emphasizes internal validity of evaluation design, such as controlled experiments. This paper describes two such trials, implemented at different times with differing social contexts for youth cigarette smoking, smoking prevention research evidence bases, and tobacco control environments. Common and unique features of the two trials are reviewed, and observations are noted about the conditions under which controlled trials of mass media interventions might be warranted.